ax-y=z

Simple and best practice solution for ax-y=z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ax-y=z equation:


Simplifying
ax + -1y = z

Solving
ax + -1y = z

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'y' to each side of the equation.
ax + -1y + y = y + z

Combine like terms: -1y + y = 0
ax + 0 = y + z
ax = y + z

Divide each side by 'x'.
a = x-1y + x-1z

Simplifying
a = x-1y + x-1z

See similar equations:

| a=15-8 | | x^3+-10x^2-8=0 | | x-20(9)=7x | | 67+(3x+14)=90 | | 3y=44-19y | | c=0.17(6)+0.63 | | 9+x=3x-12 | | w/5-16=7 | | -1x=5x | | 7+m=25 | | V-5/5=-7/8 | | 24b=8whatisb | | 3.2x+4.5x+3-2=-2.2+5x-7 | | A-100=0 | | X/6-(-10)=4 | | 13.95*6.25%= | | 9i/(9-8i) | | f(x)=(x+4)(x-4)(x-9) | | i/2=-2 | | 5+k=10 | | 8x^2=12y | | 20-8x=-68 | | 37/210= | | 150=3+5w | | 6-2y=4+3y | | 1/4t=240 | | 5y(2y-3)=(2y-3) | | 8/7= | | x+56=90 | | 9/23= | | t=240 | | 3x-2Y=5XY |

Equations solver categories